Generalizations of the standard Artin representation are unitary - Mohammad N. Abdulrahim (International Journal of Mathematics and Mathematical Sciences)
We consider the Magnus representation of the image of the braid group under the generalizations of the standard Artin representation discovered by M. Wada. We show that the images of the generators of the braid group under the Magnus representation are unitary relative to a Hermitian matrix. As a special case, we get that the Burau representation is unitary, which was known and proved by C. C. Squier.